Integrated physical-layer secure visible light communication and positioning system based on polar codes - Fang, Junbin; Pan, Junxing; Huang, Xia; Lin, Jiajun; Jiang, Canjian (Optics express, 2023)
Visible light communication (VLC) with physical-layer security can provide information-theoretic security for the optical wireless channel based on the characteristics of the channel instead of encryption algorithms and secret keys at application layer. Since precise location information of communication parties is crucial for estimating channel states and designing secure communication schemes, this paper proposes an integrated visible light communication and positioning system which provides triple functionalities of high-accuracy indoor positioning, physical-layer secure visible light communication, and flicker mitigation illumination. A heterogeneous signal hybrid line coding scheme is proposed for the transmitter to converge the high-speed communication data signals and the low-speed positioning data signals, and a hybrid heterogeneous signal extraction scheme is proposed for the receiver to separate the hybrid heterogeneous signals with a high-bandwidth photodetector and a low-pass complementary metal-oxide-semiconductor (CMOS) image sensor. Based on the positioning information and the communication scheme, a polar codes-based forward error correction coding scheme is designed to achieve physical-layer security and transmission reliability simultaneously. Numerical results show that the proposed system can reach a secrecy code rate of 0.76 for a single-input single-output indoor VLC channel and a transmission efficiency of 0.38 without perceivable flicker. Experimental results show that the proposed system can achieve an average positioning accuracy of 3.35 cm and decrease the bit error rate of a legitimate receiver to a near error-free level (lower than 10 −7 ) while keeping the bit error rate of an eavesdropper at 0.4887 (nearly 0.5) with a transmission data rate of 1 Mbps, resulting in near-zero suppression of the eavesdropped information and a high secrecy capacity of 0.9994.